Exploring the Impacts of Student-Led Sustainability Projects with Secondary School Students and Teachers - Rosvita, Indah (UM Purwokerto Press, 2025)
Student-led sustainability projects are essential in promoting environmental awareness and community engagement. This research aims to understand the implications of such projects on student learning, teacher roles, community engagement, and project assessment. The methodology involves collaborative planning, execution, and assessment of the projects, utilizing qualitative data analysis from student focus groups, teacher responses, and project meetings. The results highlight the development of practical skills and competencies, aligning with current trends in education. These projects not only contribute to immediate environmental and social outcomes but also foster a long-term culture of environmental responsibility within the school and the broader community. The emphasis on practical education and the development of softer skills aligns with the broader shift in education towards promoting not only academic achievement but also the development of practical skills and competencies. This research opens up possibilities for further exploration of the impacts of student-led sustainability projects on holistic student development and community sustainability efforts. Overall, this research contributes to ongoing discussions about education’s purpose and the role of schools in promoting sustainable development.